2005
DOI: 10.1038/nature03484
|View full text |Cite
|
Sign up to set email alerts
|

Advanced optics in a jellyfish eye

Abstract: Cubozoans, or box jellyfish, differ from all other cnidarians by an active fish-like behaviour and an elaborate sensory apparatus. Each of the four sides of the animal carries a conspicuous sensory club (the rhopalium), which has evolved into a bizarre cluster of different eyes. Two of the eyes on each rhopalium have long been known to resemble eyes of higher animals, but the function and performance of these eyes have remained unknown. Here we show that box-jellyfish lenses contain a finely tuned refractive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
162
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(174 citation statements)
references
References 22 publications
10
162
0
2
Order By: Relevance
“…Therefore, we concluded that the box jellyfish opsin forms a photosensitive pigment with similar characteristics in photoisomerization profile and with differences in the photoproduct property, which is involved in the G protein activation, to the visual pigments of higher animals, such as insects, molluscs, and vertebrates. Each rhopalium of the box jellyfish contains two highly sophisticated lens eyes, upper small lens eye and lower large lens eye, in addition to two pairs of simple pit eyes (14,16,23) (Fig. S1B).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we concluded that the box jellyfish opsin forms a photosensitive pigment with similar characteristics in photoisomerization profile and with differences in the photoproduct property, which is involved in the G protein activation, to the visual pigments of higher animals, such as insects, molluscs, and vertebrates. Each rhopalium of the box jellyfish contains two highly sophisticated lens eyes, upper small lens eye and lower large lens eye, in addition to two pairs of simple pit eyes (14,16,23) (Fig. S1B).…”
Section: Resultsmentioning
confidence: 99%
“…Because the visual fields of individual eyes of the rhopalium partly overlap, Tripedalia (like other Cubomedusae) has an almost complete view of its surroundings. The lenscontaining Tripedalia eyes have sophisticated visual optics as do advanced bilaterian phyla (11).…”
mentioning
confidence: 99%
“…For organisms with the simplest types of nervous systems, we can observe that the integration of different sensory channels is kept to a minimum, as required for instant motor control and action selection. An example is Cubozoans or box jelly fishes, which possess 24 eyes of 4 different types, where each type presumably serves a different adaptive function (Nilsson et al 2005;Jacobs et al 2007). Computationally more thorough degrees of informational or conceptual integration in organisms with multiple sets of eyes can be found at higher evolutionary levels of neural organisation (e.g.…”
Section: Biological Plausibility Of Conceptual Formsmentioning
confidence: 99%